Composite sand solidification agent and preparation method thereof

By copolymerizing cellulose and chitosan and loading fly ash and silicate clinker hydrate, a composite sand-fixing agent is formed, which solves the problems of low strength, long curing time, and poor water retention performance of existing sand-fixing agents, and achieves high efficiency , environmentally friendly desertification control effect.

CN119351112APending Publication Date: 2025-01-24JIANGSU JIEFENG CONSTRUCTION ENGINEERING CO LTD

Patent Information

Application Number
CN202411417314.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the treatment of desertification, existing chemical sand fixing agents have problems such as low strength, long curing time, poor water retention performance and potential pollution to the environment, and it is difficult to meet the efficient and environmentally friendly sand control needs.

Method used

After the fibrin modified, the chitosaccharides are together to form a polycatic hydroxyl club with a three -dimensional mesh structure, and the coal ash and silicate ripening hydrophilizer in the consecutive polymers form a composite sand fixing agent. This method improves the water absorption performance, mechanical strength and adhesiveness of the sandwiches.

Benefits of technology

The prepared composite sand-fixing agent has high strength and excellent water-retaining and sand-fixing capabilities, and is environmentally friendly. The later degradation of the sand-fixing material will have no obvious negative impact on the ecological environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079796040000051
    Figure BDA0005079796040000051
  • Figure BDA0005079796040000061
    Figure BDA0005079796040000061
Patent Text Reader

Abstract

The invention relates to the field of environmental protection, and discloses a composite sand solidification agent and a preparation method thereof. The cellulose-chitosan composite material comprises the following components: 40-50 parts of cellulose, 80-100 parts of chitosan, 2-4 parts of a cross-linking agent, 1-2 parts of an initiator, 2-4 parts of a dispersant, 20-30 parts of fly ash, 20-30 parts of silicate clinker, 200-240 parts of a sodium hydroxide solution, 10-15 parts of sodium carbonate, 80-100 parts of an ethanol solution of chloroacetic acid, 250-300 parts of a sodium acetate buffer solution, 80-100 parts of ethanol, 240-320 parts of ethylene glycol and 30-40 parts of water. The cellulose is modified and then copolymerized with the chitosan, then the copolymer is loaded with the fly ash and the silicate clinker hydrate, the prepared composite sand solidification agent has high strength and excellent water absorption and retention capacity and is environmentally friendly, and the raw materials cellulose and chitosan are derived from biological raw materials, are wide in source, are easy to degrade and are free of toxicity and pollution; the fly ash is subjected to roasting pretreatment, and degradation of the sand stabilization material in the later period has no obvious negative effect on the ecological environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental protection, and in particular to a composite sand-fixing agent and a preparation method thereof. Background Art

[0002] Desertification is one of the three most serious problems facing the world today. It can be categorized into the following types: soil erosion, desertification, and salinization. Desertification, the most prevalent hazard facing my country, severely damages the physical and chemical properties of the soil. This not only leads to a loss of land productivity but also severely deteriorates the natural environment due to the formation of sandy land. Desertification severely hinders economic development and the improvement of people's quality of life and living conditions. Consequently, inexpensive, convenient, efficient, and environmentally friendly chemical sand control and fixation materials have become a hot topic of interest.

[0003] Chemical sand-fixing agents can be primarily categorized as inorganic sand-fixing materials, polymer sand-fixing materials, and organic-inorganic composite sand-fixing materials. Cement and water glass are the most widely studied inorganic sand-fixing materials. Cement-based sand-fixing agents utilize the capping effect of cement solidification. However, due to the lack of water in deserts, cement produces fewer hydration products, resulting in poor solidification. Furthermore, due to its lack of toughness, cement easily shrinks, thus losing its sand-fixing effectiveness. Water glass-based sand-fixing agents act as gels, but are less resistant to water. Under alkaline conditions, their curing effect worsens, resulting in lower strength of the cured layer and a high risk of secondary alkaline pollution. Polymer sand-fixing materials are essentially water- or oil-soluble polymer chemical cements. Due to their stable adhesive properties and excellent water-retention and absorption capabilities, these sand-fixing agents offer numerous advantages, including rapid onset, effective results, strong water-retention and water-resistance, and strong wind-erosion resistance. However, their disadvantages are that some polymers are difficult to degrade or can be harmful to the environment if degraded. If not properly handled, large areas of sand-fixing materials left on the surface can pose a threat comparable to desertification. Organic-inorganic composite sand-fixing materials are a new type of composite sand-fixing material formed by adding organic components to inorganic materials to address the defects of inorganic sand-fixing materials such as low strength, poor mechanical properties, and lack of water retention. The synthesized material has higher flexural strength, bonding strength, impact resistance and fatigue resistance.

[0004] Patent CN110330980 provides a degradable, self-repairing water-retaining and sand-fixing agent and its preparation method. This method involves preparing a hydrogel from acrylamide, xanthan gum, and other ingredients, refining and modifying polyurethane powder with stearic acid to form microcapsules, and then compounding the resulting sand-fixing agent. The polyurethane prepared by this method has excellent film-forming properties, but the polyurethane-modified sand-fixing agent is difficult to biodegrade. Patent application number CN2020107166821 discloses an environmentally friendly keratin-based sand-fixing agent and its preparation method. This combines the treatment of livestock and poultry hair waste with the control of sand and dust pollution, solving the problem of chemical sand-fixing agents being retained and affecting the environment while also providing new ideas for the resource utilization of livestock and poultry hair solid protein. However, the sand-fixing agent prepared by this method has low strength, a long curing time, and poor water retention, failing to meet user needs for a sand-fixing agent. Summary of the Invention

[0005] In order to overcome the shortcomings and deficiencies of the existing technology, the present invention aims to provide a composite sand-fixing agent and a preparation method thereof. The prepared composite sand-fixing agent has high strength and excellent water-retention and sand-fixing capabilities, and is environmentally friendly. The subsequent degradation of the sand-fixing material has no obvious negative impact on the ecological environment.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A composite sand-fixing agent comprises, by weight, 40-50 parts of cellulose, 80-100 parts of chitosan, 2-4 parts of a cross-linking agent, 1-2 parts of an initiator, 2-4 parts of a dispersant, 20-30 parts of fly ash, 20-30 parts of silicate clinker, 200-240 parts of a sodium hydroxide solution, 10-15 parts of sodium carbonate, 80-100 parts of an ethanol solution of chloroacetic acid, 250-300 parts of a sodium acetate buffer solution, 80-100 parts of ethanol, 240-320 parts of ethylene glycol, and 30-40 parts of water.

[0008] Preferably, the cross-linking agent is DCP.

[0009] Preferably, the initiator is potassium persulfate.

[0010] Preferably, the dispersant is one of sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.

[0011] Preferably, the silicate clinker is a mixture of tricalcium silicate, dicalcium silicate, tricalcium aluminate, tetracalcium aluminoferrite and ash mixed material.

[0012] Preferably, the silicate clinker is composed of 35-60% tricalcium silicate, 15-35% dicalcium silicate, 7-15% tricalcium aluminate, 10-18% tetracalcium aluminoferrite, and the remainder is ash mixed material.

[0013] Preferably, the concentration of the sodium hydroxide solution is 10%, and the concentration of the chloroacetic acid ethanol solution is 50%.

[0014] The preparation method of the composite sand-fixing agent comprises the following steps:

[0015] (1) Dissolve cellulose in 2 times its weight of ethanol, add sodium hydroxide solution and stir for 1 hour, then add chloroacetic acid ethanol solution and heat. After the reaction is complete, neutralize with hydrochloric acid to pH 7, filter, wash with ethanol, and dry to obtain modified cellulose;

[0016] (2) dissolving the modified cellulose and chitosan in a sodium acetate buffer solution, adding a crosslinking agent, an initiator, and a dispersant, heating to 55° C. and reacting for 3 h. After the reaction is complete, filtering, washing with deionized water, and drying to obtain a copolymer of the modified cellulose and chitosan;

[0017] (3) mixing fly ash and sodium carbonate uniformly and then calcining at high temperature to obtain a fly ash pretreatment product;

[0018] (4) Ethylene glycol and water are mixed evenly to form a mixed solution, and then copolymer, fly ash pretreatment material, and silicate clinker are added and stirred for reaction for 3 hours, filtered, and the ethylene glycol is evaporated and filtered again, washed with deionized water, and dried to obtain a composite sand-fixing agent.

[0019] Preferably, the heating temperature in step (1) is 75° C. and the reaction time is 2-3 h.

[0020] Preferably, the weight ratio of ethylene glycol to water in the mixed solution of ethylene glycol and water in step (4) is 8:1.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides an organic-inorganic composite sand-fixing agent and a preparation method thereof. The present invention copolymerizes modified cellulose with chitosan to obtain a polyhydroxy copolymer having a three-dimensional network structure, thereby improving the water absorption and water retention properties of the sand-fixing agent. The modified cellulose has a stable structure and high mechanical strength and toughness. In addition, the copolymer is loaded with fly ash and silicate clinker hydrate, which can undergo a gelation reaction with ordinary sand, further improving the strength and adhesion of the sand-fixing agent. The raw materials cellulose and chitosan used in the present invention are derived from biological raw materials, which are widely available, easily degradable, and non-toxic and pollution-free. The fly ash is pre-treated by roasting, and the resulting composite sand-fixing agent is environmentally friendly, and the subsequent degradation of the sand-fixing material has no significant negative impact on the ecological environment. DETAILED DESCRIPTION

[0023] The following will clearly and completely describe the concept and technical effects of the present invention in conjunction with the embodiments so as to fully understand the purpose, characteristics and effects of the present invention.

[0024] Example 1:

[0025] A composite sand-fixing agent comprises, by weight, 40 parts of cellulose, 80 parts of chitosan, 2 parts of DCP, 1 part of potassium persulfate, 2 parts of sodium pyrophosphate, 20 parts of fly ash, 20 parts of silicate clinker, 200 parts of sodium hydroxide solution, 10 parts of sodium carbonate, 80-100 parts of chloroacetic acid ethanol solution, 250 parts of sodium acetate buffer solution, 80 parts of ethanol, 240 parts of ethylene glycol, and 30 parts of water.

[0026] The preparation method of the composite sand-fixing agent described in this embodiment is as follows:

[0027] (1) Dissolve cellulose in 2 times its weight of ethanol, add sodium hydroxide solution and stir for 1 hour, then add chloroacetic acid ethanol solution, heat to 75°C, react for 2 hours, and after the reaction is completed, neutralize with hydrochloric acid to pH 7, filter, wash with ethanol, and dry to obtain modified cellulose;

[0028] (2) Dissolving the modified cellulose and chitosan in a sodium acetate buffer solution, adding DCP, potassium persulfate, and sodium pyrophosphate, heating to 55°C and reacting for 3 hours, filtering after the reaction, washing with deionized water, and drying to obtain a copolymer of the modified cellulose and chitosan;

[0029] (3) mixing fly ash and sodium carbonate uniformly and then calcining at high temperature to obtain a fly ash pretreatment product;

[0030] (4) Ethylene glycol and water in a weight ratio of 8:1 were mixed evenly to form a mixed solution, and then the copolymer, fly ash pretreatment material, and silicate clinker were added and stirred for 3 hours, filtered, and the ethylene glycol was evaporated and filtered again, washed with deionized water, and dried to obtain a composite sand fixation agent.

[0031] Example 2:

[0032] A composite sand-fixing agent comprises, by weight, 45 parts of cellulose, 90 parts of chitosan, 3 parts of DCP, 1 part of potassium persulfate, 3 parts of sodium tripolyphosphate, 25 parts of fly ash, 25 parts of silicate clinker, 220 parts of sodium hydroxide solution, 12 parts of sodium carbonate, 90 parts of chloroacetic acid ethanol solution, 275 parts of sodium acetate buffer solution, 90 parts of ethanol, 280 parts of ethylene glycol, and 35 parts of water.

[0033] The preparation method of the composite sand-fixing agent described in this embodiment is as follows:

[0034] (1) Dissolve cellulose in 2 times its weight of ethanol, add sodium hydroxide solution and stir for 1 hour, then add chloroacetic acid ethanol solution, heat to 75°C, react for 2-3 hours, and after the reaction is completed, neutralize with hydrochloric acid to pH 7, filter, wash with ethanol, and dry to obtain modified cellulose;

[0035] (2) Dissolving the modified cellulose and chitosan in a sodium acetate buffer solution, adding DCP, potassium persulfate, and sodium tripolyphosphate, heating to 55° C. and reacting for 3 h, filtering after the reaction, washing with deionized water, and drying to obtain a copolymer of the modified cellulose and chitosan;

[0036] (3) mixing fly ash and sodium carbonate uniformly and then calcining at high temperature to obtain a fly ash pretreatment product;

[0037] (4) Ethylene glycol and water in a weight ratio of 8:1 were mixed evenly to form a mixed solution, and then the copolymer, fly ash pretreatment material, and silicate clinker were added and stirred for 3 hours, filtered, and the ethylene glycol was evaporated and filtered again, washed with deionized water, and dried to obtain a composite sand fixation agent.

[0038] Example 3:

[0039] A composite sand-fixing agent comprises, by weight, 50 parts of cellulose, 100 parts of chitosan, 4 parts of DCP, 2 parts of potassium persulfate, 4 parts of sodium hexametaphosphate, 30 parts of fly ash, 30 parts of silicate clinker, 240 parts of sodium hydroxide solution, 15 parts of sodium carbonate, 100 parts of chloroacetic acid ethanol solution, 300 parts of sodium acetate buffer solution, 100 parts of ethanol, 320 parts of ethylene glycol, and 40 parts of water.

[0040] The preparation method of the composite sand-fixing agent described in this embodiment is as follows:

[0041] (1) Dissolve cellulose in 2 times its weight of ethanol, add sodium hydroxide solution and stir for 1 hour, then add chloroacetic acid ethanol solution, heat to 75°C, react for 2-3 hours, and after the reaction is completed, neutralize with hydrochloric acid to pH 7, filter, wash with ethanol, and dry to obtain modified cellulose;

[0042] (2) Dissolving the modified cellulose and chitosan in a sodium acetate buffer solution, adding DCP, potassium persulfate, and sodium hexametaphosphate, heating to 55° C. and reacting for 3 h, filtering after the reaction, washing with deionized water, and drying to obtain a copolymer of the modified cellulose and chitosan;

[0043] (3) mixing fly ash and sodium carbonate uniformly and then calcining at high temperature to obtain a fly ash pretreatment product;

[0044] (4) Ethylene glycol and water in a weight ratio of 8:1 were mixed evenly to form a mixed solution, and then the copolymer, fly ash pretreatment material, and silicate clinker were added and stirred for 3 hours, filtered, and the ethylene glycol was evaporated and filtered again, washed with deionized water, and dried to obtain a composite sand fixation agent.

[0045] Comparative Example 1:

[0046] The only difference between this comparative example and Example 1 is that modified cellulose is not added in step (2), and the remaining raw materials and steps are the same as those in Example 1.

[0047] Comparative Example 2:

[0048] The only difference between this comparative example and Example 1 is that chitosan is not added in step (2), and the remaining raw materials and steps are the same as those in Example 1.

[0049] Comparative Example 3:

[0050] The only difference between this comparative example and Example 1 is that no fly ash pretreatment material is added in step (4), and the remaining raw materials and steps are the same as those in Example 1.

[0051] Sand fixation agent performance test:

[0052] 1. Sand fixation agent strength test: Take 6 parallel sand samples, spray them with equal amounts of sand fixation agent, and then evenly spray them with equal amounts of water. Measure the strength and thickness of the solidified layer formed. The data are shown in Table 1.

[0053] Table 1: Sand fixation agent strength test

[0054] Cured layer strength / MPa Cured layer thickness / cm Example 1 2.11 1.2 Example 2 2.07 1.2 Example 3 2.36 1.3 Comparative Example 1 1.54 0.6 Comparative Example 2 2.16 1.1 Comparative Example 3 1.36 0.5

[0055] As can be seen from the table above, the solidified layer of Comparative Example 1 is weaker in strength and thinner in thickness than that of Example 1. This is because no modified cellulose was added in Comparative Example 1, while modified cellulose was added in Example 1. The modified cellulose has a stable structure, high mechanical strength and toughness, and improves the strength of the sand-fixing agent. The solidified layer of Comparative Example 3 is weaker in strength and thinner in thickness than that of Example 1. This is because no fly ash pretreatment was added in Comparative Example 3, while fly ash pretreatment was added in Example 1, which reacted with ordinary sand to form a gel, further improving the strength and adhesion of the sand-fixing agent.

[0056] 2. Test of water retention of sand-fixing agent: Take 7 parallel sand samples, spray 6 of them with equal amounts of sand-fixing agent sample, and leave one as a blank control group. Then spray the sand evenly with equal amounts of water so that the initial moisture content of the sand is 30%. After placing the sand at a temperature of about 20°C for 7 days, calculate the moisture content; after placing it for 30 days, test the moisture content again. The data are shown in Table 2.

[0057] Table 2: Water retention test of sand fixation agent

[0058]

[0059]

[0060] As can be seen from the above table, the moisture content of Comparative Example 2 at 7 days and 30 days is lower than that of Example 1. This is because no chitosan is added in Comparative Example 1, while chitosan is added in Example 1 and copolymerized with modified cellulose to obtain a polyhydroxy copolymer with a three-dimensional network structure, which makes the sand fixation agent have excellent water absorption and water retention properties.

[0061] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A composite sand-fixing agent, characterized in that: The raw materials include, by weight, 40-50 parts of cellulose, 80-100 parts of chitosan, 2-4 parts of a crosslinking agent, 1-2 parts of an initiator, 2-4 parts of a dispersant, 20-30 parts of fly ash, 20-30 parts of silicate clinker, 200-240 parts of a sodium hydroxide solution, 10-15 parts of sodium carbonate, 80-100 parts of an ethanol solution of chloroacetic acid, 250-300 parts of a sodium acetate buffer solution, 80-100 parts of ethanol, 240-320 parts of ethylene glycol and 30-40 parts of water.

2. A composite sand fixation agent according to claim 1, characterized in that: The cross-linking agent is DCP.

3. A composite sand-fixing agent according to claim 1, characterized in that: The initiator is potassium persulfate.

4. A composite sand-fixing agent according to claim 1, characterized in that: The dispersant is one of sodium pyrophosphate, sodium tripolyphosphate and sodium hexametaphosphate.

5. A composite sand-fixing agent according to claim 1, characterized in that: The silicate clinker is a mixture of tricalcium silicate, dicalcium silicate, tricalcium aluminate, tetracalcium aluminoferrite and ash mixed materials.

6. A composite sand-fixing agent according to claim 5, characterized in that: The silicate clinker is composed of 35-60% tricalcium silicate, 15-35% dicalcium silicate, 7-15% tricalcium aluminate, 10-18% tetracalcium aluminoferrite, and the rest is ash mixed material.

7. A composite sand-fixing agent according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 25%, and the concentration of the chloroacetic acid ethanol solution is 50%.

8. A method for preparing a composite sand-fixing agent according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) dissolving cellulose in ethanol twice its weight, adding sodium hydroxide solution and stirring for 1 hour, then adding ethanol solution of chloroacetic acid and heating, neutralizing with hydrochloric acid to pH 7 after the reaction, filtering, washing with ethanol, and drying to obtain modified cellulose; (2) dissolving the modified cellulose and chitosan in a sodium acetate buffer solution, adding a crosslinking agent, an initiator, and a dispersant, heating to 55° C. for reaction for 3 h, filtering after the reaction is completed, washing with deionized water, and drying to obtain a copolymer of the modified cellulose and chitosan; (3) mixing fly ash and sodium carbonate uniformly and then calcining at high temperature to obtain a fly ash pretreatment product; (4) Ethylene glycol and water are mixed evenly to form a mixed solution, and then the copolymer, fly ash pretreatment material, and silicate clinker are added and stirred for reaction for 3 hours, filtered, and the ethylene glycol is evaporated and filtered again, washed with deionized water, and dried to obtain a composite sand-fixing agent.

9. The method for preparing a composite sand-fixing agent according to claim 8, characterized in that: The heating temperature in step (1) is 75° C. and the reaction time is 2-3 h.

10. The method for preparing a composite sand-fixing agent according to claim 8, characterized in that: The weight ratio of ethylene glycol to water in the mixed solution of ethylene glycol and water in step (4) is 8:1.

Citation Information

Patent Citations

  • Environmental-friendly soil stabilizer

    CN106497575A

  • Method for producing composite liquid mulching films from straw

    CN106832430A

  • Method for preparing sand fixing agents

    CN107033919A

  • Sand fixing agent as well as preparation method, use method and application thereof

    CN108865150A

  • Preparation method of long-acting sand-fixing agent

    CN108865155A

Cited By

  • Multifunctional wind-prevention and sand-fixation agent for salinization area, preparation method and use method of multifunctional wind-prevention and sand-fixation agent

    CN120399712A

  • Inorganic quartzite plate and preparation method thereof

    CN121850529A